The MCP-1 -2518 (A to G) single nucleotide polymorphism is not associated with myocardial infarction in the Czech population - Cermakova, Z; Petrkova, J; Arakelyan, A; Drabek, J; Mrazek, F; Lukl, J; Petrek, M (International journal of immunogenetics, 2005)
Monocyte chemoattractant protein (MCP)-1 is the key chemokine in the process of atheroslerotic vascular inflammation. Examining already reported association between coronary artery disease (CAD) and the SNP A/G in the MCP-1 gene (position -2518), 139 Czech patients with CAD manifested as myocardial infarction (MI) and 359 unrelated healthy control (C) subjects were genotyped by PCR-SSP. Genotype and allele frequencies were not different in MI and C groups (allele G: MI, 20.5%; C, 23.8%, OR = 0.8, P > 0.05). No differences were detected when the patients were subdivided based on sex or the age of MI first occurrence. Further, no relationship was observed between circulating MCP-1 levels and carriage of the G allele. The data do not support a role for the MCP-1 -2518 single nucleotide polymorphism in susceptibility to CAD manifested by myocardial infarction.
Keywords: Female; ženské pohlaví; jednonukleotidový polymorfismus; Predictive Value of Tests; koronární nemoc; prediktivní hodnota testů; lidé; Coronary Disease; Polymorphism, Single Nucleotide; genetická predispozice k nemoci; Genetic Predisposition to Disease; chemokin CCL2; Male; Chemokine CCL2; alely; Myocardial Infarction; Alleles; lidé středního věku; mužské pohlaví; Middle Aged; infarkt myokardu; Humans